Metadata Collaboration between the Swiss National Library and Research Institutions in the Field of Swiss Historiography. Issue 1 (2nd January 2019) - von Wartburg, Karin; Sibille, Christiane; Aliverti, Christian
Abstract: This article presents examples of metadata collaborations between the Swiss National Library (NL) and research institutions in the field of Swiss historiography. The NL publishes the Bibliography on Swiss History (BSH). In order to meet the demands of its research community, the NL has improved the accessibility and interoperability of the BSH database. Moreover, the BSH takes part in metadata projects such as Metagrid, a web service linking different historical databases. Other metadata collaborations with partners in the historical field such as the Law Sources Foundation (LSF) will position the BSH as an indispensable literature hub for publications on Swiss history.